Amphiphilic Ti3C2Tx-based flexible nanosheet oil-displacing agent and preparation method thereof

By introducing hydrophobic segments onto the surface of Ti3C2Tx nanosheets, amphiphilic nanosheets were prepared, solving the problem of low contact efficiency of traditional nanomaterials at the oil-water interface and achieving a high-efficiency improvement in crude oil recovery.

CN120966446AActive Publication Date: 2025-11-18SOUTHWEST PETROLEUM UNIV
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511490571.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-17
Publication Date
2025-11-18
Estimated Expiration
2045-10-17

AI Technical Summary

Technical Problem

Traditional nanomaterials have small specific surface area, are prone to aggregation, require high concentrations, have low contact efficiency with the oil-water interface, and offer limited improvement in oil recovery, making it difficult to effectively enhance crude oil recovery.

Method used

By introducing hydrophobic segments onto the surface of Ti3C2Tx nanosheets, amphiphilic Ti3C2Tx-based flexible nanosheets are prepared. These nanosheets are then used to self-assemble into films at the oil-water interface, forming a large-structure separation pressure and strong oil-scooping ability, thereby improving crude oil recovery.

Benefits of technology

It effectively improves crude oil recovery at ultra-low concentrations. The large contact area between the nanosheets and the interface forms a stable emulsion, enhancing the oil displacement effect.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120966446A_ABST
    Figure CN120966446A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of oil and gas exploitation and oilfield chemistry, and relates to an amphiphilic Ti3C2Tx-based flexible nanosheet oil-displacing agent and a preparation method thereof. The preparation method comprises the following steps: taking Ti3AlC2 as a raw material, preparing a single-layer / few-layer flexible Ti3C2Tx nanosheet by utilizing a modified acid (hydrochloric acid and lithium fluoride) etching method, and further performing chemical modification on the single-layer / few-layer flexible Ti3C2Tx nanosheet by utilizing a hydrophobic silane coupling agent to prepare the amphiphilic Ti3C2Tx-based flexible nanosheet. By introducing the hydrophobic chain segment, the prepared amphiphilic Ti3C2Tx-based flexible nanosheet has the property of changing an oil-water interface and the oil shoveling capacity, is suitable for water injection development operation of oil and gas fields, and can effectively improve the crude oil recovery rate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of oil and gas extraction and oilfield chemistry technology, and relates to an amphiphilic Ti3C2T x Flexible nanosheet oil displacement agent and its preparation method. Background Technology

[0002] In recent years, nanomaterial-based enhanced oil recovery (EOR) has become a research hotspot. Fluids based on nanomaterials can enhance EOR through various mechanisms, including altered wettability, reduced oil-water interfacial tension, in-situ Pickering emulsion formation, and the generation of structural separation pressures. Traditional nanomaterial research has mainly focused on zero-dimensional spherical nanoparticles (such as SiO2, TiO2, Al2O3, CuO, ZnO, etc.). However, compared to rigid zero-dimensional particulate nanomaterials, flexible two-dimensional nanosheets have greater deformability, are more easily inserted into nanoscale pores, displacing crude oil without clogging the pores.

[0003] Ti3C2T x Nanosheets, a novel nanomaterial discovered in 2011, have been widely applied in energy storage, sensing, optoelectronics, catalysis, environmental remediation, oil-water separation, and biomedicine; however, regarding Ti3C2T... x Research on nanosheets as oil displacement agents in the field of enhanced oil recovery is in its early stages. This research focuses on Ti3C2T... x Modifying nanosheets with hydrophobic groups can prevent the formation of pristine Ti3C2T. x Oxidation and endowment of Ti3C2T x The nanosheets are amphiphilic to enhance their interaction with oil and water interfaces. Simultaneously, Ti3C2T... x Two-dimensional flexible nanosheets possess a larger specific surface area and more active sites, facilitating "face-to-face" contact with fluids. Their confined rotation at the liquid-liquid interface leads to directional adsorption, making them more conducive to the formation of stable emulsions than spherical nanoparticles. Furthermore, nanosheets can form "wedge-shaped films" at lower concentrations, exhibiting excellent oil displacement effects. In oil displacement technology, many interfacial interactions (oil / water and liquid / rock interfaces) are inherently two-dimensional; therefore, compared to spherical materials, sheet-like materials can form a larger contact area with the interface, making them highly promising for enhanced oil recovery applications.

[0004] To address the technical bottlenecks of traditional nanomaterials, such as small specific surface area, easy aggregation, high concentration, low contact efficiency with oil-water interface, and limited recovery improvement, this invention is based on Ti3C2T. x The preparation of novel nanofluids for oil displacement by hydrophobic modification of flexible nanosheets provides a more efficient and reliable new method for improving crude oil recovery. Summary of the Invention

[0005] This invention utilizes Ti3C2T x The principle is based on the fact that surface hydroxyl groups can undergo a condensation reaction with the silanol groups after hydrolysis of the silane coupling agent to form a covalent bond "Ti-O-Si"; by selecting a hydrophobic silane coupling agent, in Ti3C2T x Amphiphilic Ti3C2T was prepared by introducing hydrophobic segments onto the surface and rationally controlling the ratio of hydrophilic to hydrophobic groups. x Flexible nanosheets are formulated into nanofluids for oil displacement; they can self-assemble into films at the oil-water interface at ultra-low concentrations, possessing both high structural separation pressure and strong oil-scooping ability, which can effectively improve crude oil recovery.

[0006] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: an amphiphilic Ti3C2T x Flexible nanosheet-based oil displacement agent and its preparation method include the following steps: Step 1: By weight, add 8 parts of lithium fluoride and 100-120 parts of 12 mol / L hydrochloric acid to the reactor, heat to 40℃-50℃, and stir at a constant temperature for 15-20 min; weigh 5 parts of Ti3AlC2 and slowly add it to the reactor, stirring and reacting for 24-48 h; wash the obtained product successively with dilute hydrochloric acid and distilled water by centrifugation until the pH of the supernatant reaches about 6, thus obtaining multilayer Ti3C2T. x Nanosheets; Step 2: Centrifuge and wash the nanosheets obtained in Step 1 until the supernatant is black. Replace the distilled water with anhydrous ethanol and purge with nitrogen for 2-3 minutes. Sonicate in an ice bath for 1-2 hours. Centrifuge at 3500-5000 rpm for 15-30 minutes. The resulting black supernatant is the monolayer / few-layer Ti3C2T dispersed in the ethanol solution. x The solid content is 30%~60%; Step 3: Add the Ti3C2T obtained in Step 2 to the container. x Dispersion 20 parts of silane coupling agent, 16-24 parts of distilled water, and 1-2 parts of silane coupling agent were reacted with acetic acid to adjust the pH to approximately 3, and stirred at room temperature for 12-24 hours. The resulting product was washed multiple times by centrifugation with anhydrous ethanol and freeze-dried for 24-48 hours to obtain amphiphilic Ti3C2T modified with silane coupling agent. x Flexible nanosheets; Step 4: Using distilled water as the dispersion, prepare nanofluid oil displacement agents of different concentrations using the product obtained in Step 3. Stir at room temperature for 4-8 hours at 600-800 rpm, followed by sonication in an ice bath for 1-2 hours to obtain amphiphilic Ti3C2T. xFlexible nanosheet oil displacement agent.

[0007] Further, in step three, the silane coupling agent is [3-(methacryloyloxy)propyl]trimethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, isobutyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, and phenyltrimethoxysilane.

[0008] The present invention also provides an amphiphilic Ti3C2T x The application of amphiphilic nanosheets as an oil displacement agent in the field of enhanced oil recovery, wherein the mass concentration of the amphiphilic nanosheets is 0.003%~0.02%.

[0009] The beneficial effects of this invention are: The Ti3C2T of the present invention x The flexible nanosheets possess a large specific surface area and multiple active sites. Simultaneously, the introduced hydrophobic segments of the silane coupling agent endow the nanosheets with amphiphilicity. The amphiphilic flexible nanosheets can be effectively adsorbed at the oil-water interface, achieving "face-to-face" contact with the oil-water interface, thereby improving the properties of the oil-water interface. This provides a more efficient and reliable solution for improving crude oil recovery and has broad application prospects. Attached Figure Description

[0010] Figure 1 Single-layer / few-layer Ti3C2T x and amphiphilic nanosheets KH570@Ti3C2T x XPS spectra; Figure 2 Single-layer / few-layer Ti3C2T x and amphiphilic nanosheets KH570@Ti3C2T x XRD patterns; Figure 3 Single-layer / few-layer Ti3C2T x (a) and amphiphilic nanosheets KH570@Ti3C2T x (b) Transmission electron micrograph; Figure 4 Single-layer / few-layer Ti3C2T x (a) and amphiphilic nanosheets KH570@Ti3C2T x (b) Scanning electron microscope image; Figure 5 KH570@Ti3C2T amphiphilic nanosheets x Distribution of oil-water systems; Figure 6 KH570@Ti3C2T amphiphilic nanosheets xThree-phase contact angles of the oil displacement agent (0.01wt%)-crude oil-quartz plate system at 0 min (a), 30 min (b), and 90 min (c); Figure 7 For the microscopic visualization model of saturated oil (a), formation water drive (b), and KH570@Ti3C2T x Distribution of crude oil after nanosheet fluid drive (c). Detailed Implementation

[0011] The principles and features of the present invention are described below. The examples given are only for explaining the present invention and are not intended to limit the scope of the present invention.

[0012] Unless otherwise specified, all raw materials, reagents, instruments and equipment used in this invention can be purchased from the market or prepared by existing methods.

[0013] This invention provides an amphiphilic Ti3C2T x Flexible nanosheet-based oil displacement agent and its preparation method include the following steps: Step 1: By weight, add 8 parts of lithium fluoride and 100-120 parts of 12 mol / L hydrochloric acid to the reactor, heat to 40℃-50℃, and stir at a constant temperature for 15-20 min; weigh 5 parts of Ti3AlC2 and slowly add it to the reactor, stirring and reacting for 24-48 h; wash the obtained product successively with dilute hydrochloric acid and distilled water by centrifugation until the pH of the supernatant reaches about 6, thus obtaining multilayer Ti3C2T. x Nanosheets; Step 2: Centrifuge and wash the nanosheets obtained in Step 1 until the supernatant is black. Replace the distilled water with anhydrous ethanol and purge with nitrogen for 2-3 minutes. Sonicate in an ice bath for 1-2 hours. Centrifuge at 3500-5000 rpm for 15-30 minutes. The resulting black supernatant is the monolayer / few-layer Ti3C2T dispersed in the ethanol solution. x The solid content is 30%~60%; Step 3: Add the Ti3C2T obtained in Step 2 to the container. x Dispersion 20 parts of silane coupling agent, 16-24 parts of distilled water, and 1-2 parts of silane coupling agent were reacted with acetic acid to adjust the pH to approximately 3, and stirred at room temperature for 12-24 hours. The resulting product was washed multiple times by centrifugation with anhydrous ethanol and freeze-dried for 24-48 hours to obtain amphiphilic Ti3C2T modified with silane coupling agent. x Flexible nanosheets; Step 4: Using distilled water as the dispersion, prepare nanofluid oil displacement agents of different concentrations using the product obtained in Step 3. Stir at room temperature for 4-8 hours at 600-800 rpm, followed by sonication in an ice bath for 1-2 hours to obtain amphiphilic Ti3C2T. x Flexible nanosheet oil displacement agent.

[0014] Further, in step three, the silane coupling agent is [3-(methacryloyloxy)propyl]trimethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, isobutyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, and phenyltrimethoxysilane.

[0015] The present invention also provides an amphiphilic Ti3C2T x The application of amphiphilic nanosheets as an oil displacement agent in the field of enhanced oil recovery, wherein the mass concentration of the amphiphilic nanosheets is 0.003%~0.02%.

[0016] Example 1: Preparation of amphiphilic Ti3C2T using [3-(methacryloyloxy)propyl]trimethoxysilane (KH570) as a hydrophobic silane coupling agent. x The specific implementation steps for the flexible nanosheet-based oil displacement agent are as follows: Step 1: Add 3 g of lithium fluoride and 40 mL of 12 mol / L hydrochloric acid to the reaction vessel, heat to 50℃, and stir at a constant temperature for 15 min; weigh 2 g of Ti3AlC2 and slowly add it to the reaction vessel, stirring and reacting for 48 h; wash the obtained product successively with dilute hydrochloric acid and distilled water by centrifugation until the pH of the supernatant reaches about 6, thus obtaining multilayer Ti3C2T. x Nanosheets; Step 2: Centrifuge and wash the nanosheets obtained in Step 1 until the supernatant is black. Replace the distilled water with anhydrous ethanol and purge with nitrogen for 3 min. Sonicate in an ice bath for 1.5 h, then centrifuge at 4000 rpm for 30 min. The resulting black supernatant is the monolayer / few-layer Ti3C2T dispersed in the ethanol solution. x The solid content is 38.72%; Step 3: Add the Ti3C2T obtained in Step 2 to the container. x 10 g of dispersion, 7.74 g of KH570, and 0.68 g of distilled water were added. The pH was adjusted to approximately 3 using acetic acid, and the mixture was stirred at room temperature for 12 h. The resulting product was washed multiple times by centrifugation with anhydrous ethanol and then freeze-dried for 48 h to obtain KH570-modified amphiphilic Ti3C2T. x KH570@Ti3C2T flexible nanosheets x ; Step 4: Using distilled water as the dispersion, prepare nanofluid oil displacement agents of different concentrations using the product obtained in Step 3. Stir at 800 rpm at room temperature for 6 h, and then sonicate in an ice bath for 2 h to obtain amphiphilic Ti3C2T. x Flexible nanosheet oil displacement agent.

[0017] The amphiphilic flexible nanosheets KH570@Ti3C2T prepared in the above embodiments x Molecular structure characterization was performed, and its performance in enhancing oil recovery was further evaluated. The relevant test results are as follows: 1. Amphiphilic flexible nanosheets KH570@Ti3C2T x Structural characterization (1) XPS test The monolayer / few-layer Ti3C2T prepared in the examples x and KH570@Ti3C2T amphiphilic nanosheets after chemical modification x After vacuum drying, a small amount was taken out and tested using an Escalab 250Xi+ X-ray photoelectron spectrometer. The experimental results are as follows: Figure 1 As shown.

[0018] Figure 1 Single-layer / few-layer Ti3C2T x and amphiphilic nanosheets KH570@Ti3C2T x XPS spectra; with binding energy / eV on the x-axis and relative intensity / au on the y-axis, from Figure 1 We can obtain Ti3C2T x It is composed of F, O, Ti and C elements, and KH570@Ti3C2T x The addition of Si to the structure confirms the relationship between KH570 and Ti3C2T. x Successful bonding.

[0019] (2) XRD test The monolayer / few-layer Ti3C2T prepared in the examples x and KH570@Ti3C2T amphiphilic nanosheets after chemical modification x After vacuum drying, a small amount was taken out and tested using a Bruker D8 Advance X-ray diffractometer. The experimental results are as follows: Figure 2 As shown.

[0020] Figure 2 Single-layer / few-layer Ti3C2T x and amphiphilic nanosheets KH570@Ti3C2T x XRD pattern; plotted with 2θ / ° on the x-axis and relative intensity / au on the y-axis, from Figure 2 It can be concluded that the introduction of KH570 can change the Ti3C2T x The composition is similar to that of the original Ti3C2T. x In comparison, the (002) crystal plane diffraction peak shifted slightly from 6.62° to 6.03°. This change is attributed to the difference between KH570 and Ti3C2T. x The interlayer interactions between Ti3C2T indicate that Ti3C2T x The increased interlayer spacing further confirms the KH570@Ti3C2T x Successful preparation.

[0021] (3) Transmission electron microscopy test The monolayer / few-layer Ti3C2T prepared in the examples x and KH570@Ti3C2T nanosheets after chemical modification x The nanosheets were ultrasonically dispersed in an ethanol solution and prepared on an ultrathin copper mesh. The nanosheets were then imaged using a Talos F200S G2 transmission electron microscope. The experimental results are as follows: Figure 3 As shown.

[0022] Figure 3 Single-layer / few-layer Ti3C2T x (a) and amphiphilic nanosheets KH570@Ti3C2T x (b) Transmission electron micrograph; from Figure 3 (a) It can be observed that the original Ti3C2T x It is a two-dimensional layered structure; from Figure 3 (b) It can be observed that Ti3C2T x After chemical modification with KH570, the layered structure remains intact.

[0023] (4) Scanning electron microscopy test The monolayer / few-layer Ti3C2T prepared in the examples x and KH570@Ti3C2T nanosheets after chemical modification x After vacuum drying, a small amount was taken out, sputtered with gold, and then the nanosheets were imaged using an Apreo 2C scanning electron microscope. The experimental results are as follows: Figure 4 As shown.

[0024] Figure 4 Single-layer / few-layer Ti3C2T x (a) and amphiphilic nanosheets KH570@Ti3C2T x (b) Scanning electron microscope image; from Figure 4 (a) It can be observed that the original Ti3C2T xIt has a two-dimensional layered structure, and its structure can be bent and deformed, exhibiting the "flexible" properties of nanosheets; from Figure 4 (b) It can be observed that Ti3C2T x After chemical modification with KH570, the layered structure remains intact.

[0025] 2. Amphiphilic flexible nanosheets KH570@Ti3C2T x Performance evaluation (1) Interfacial behavior of nanosheets in oil-water systems KH570@Ti3C2T x Nanosheet oil displacement agent (0.02wt%) was mixed with white oil (Sudan III staining) in a certain proportion, shaken for 5-7 seconds, and then allowed to stand. The KH570@Ti3C2T samples were then observed. x Regarding the distribution of the oil-water system, the experimental results are as follows: Figure 5 As shown.

[0026] Figure 5 KH570@Ti3C2T amphiphilic nanosheets x Distribution of oil-water systems; from Figure 5 It can be observed that the amphiphilic KH570@Ti3C2T x Nanosheets spontaneously adsorb and aggregate at the oil-water interface, forming an interfacial film of a certain thickness. When the interfacial film is gently touched with a dropper, it is observed that the film can deform without breaking, indicating that KH570@Ti3C2T x The interfacial film formed by the nanosheets at the oil-water interface exhibits certain viscoelasticity and resistance to damage. Furthermore, a climbing film was observed formed by the nanosheets on the bottle wall surface, indicating that the KH570@Ti3C2T dispersed in the aqueous phase... x Nanosheets possess high structural separation pressure, enabling them to break through the oil-water interface and climb along the bottle wall, thereby forming a climbing film that encapsulates the oil phase. This phenomenon helps to improve oil recovery.

[0027] (2) Three-phase contact angle test Place the quartz plate on the quartz trough and add KH570@Ti3C2T into the quartz trough. x Nanosheet oil displacement agent (0.01wt%) was applied until fully contacted with the quartz surface, and then crude oil droplets were injected using a bent needle syringe; the solid (quartz sheet)-liquid (crude oil)-liquid mixture (0.01wt% KH570@Ti3C2T) was measured using an SDC-350 contact angle meter. x The three-phase contact angles of the nanosheet oil displacement agent system at different times are shown in the experimental results. Figure 6 As shown.

[0028] Figure 6KH570@Ti3C2T amphiphilic nanosheets x Three-phase contact angles of the oil displacement agent (0.01 wt%)-crude oil-quartz plate system at 0 min (a), 30 min (b), and 90 min (c); from Figure 6 (a) It can be observed that in the initial stage, the oil droplets diffuse on the surface of the quartz plate, with an average contact angle of 114.09° between the oil droplets and the quartz surface; from Figure 6 (b) It can be observed that at 30 min, the average contact angle decreased to 88.98°; from Figure 6 (c) It can be observed that the average contact angle decreased to 60.19° at 90 min; this indicates that KH570@Ti3C2T x Nanosheets can enter the confined area between the quartz sheet and the crude oil, and form a "wedge-shaped film" in the area, reducing the adhesion between the crude oil and the quartz sheet, causing the oil droplets to peel off from the quartz sheet, effectively "scraping away" the crude oil.

[0029] (3) Microscopic oil displacement experiment The microscopic visualization etching model is mainly made of plexiglass and is used to simulate the pore structure of real rock cores. The cracks in the model are formed by laser etching technology, with an etching depth of 0.5 mm, a width of 2 cm, and a length of 2 cm. First, crude oil is injected into the model at a rate of 0.3 mL / min using a micro-injection pump; then, formation water (1735 mg / L Na) is injected at the same rate. + 12.3 mg / L Mg 2+ 116.8 mg / L Ca 2+ 60.9 mg / L SO4 2– 2400 mg / L Cl – 813.9 mg / LHCO3 – Total mineralization: 5139 mg / L), followed by injection of KH570@Ti3C2T x Nanosheet oil displacement agent (0.02wt%); KH570@Ti3C2T was observed using a PH50-3A43L-A optical microscope. x The migration behavior of nanosheet oil displacement agents during the process of displacing residual oil is shown in the experimental results. Figure 7 As shown.

[0030] Figure 7 For the microscopic visualization model of saturated oil (a), formation water drive (b), and KH570@Ti3C2T x Crude oil distribution after nanosheet fluid drive (c) (dark areas represent crude oil); from Figure 7 (a) It can be observed that the crude oil has completely filled all the pore channels; from Figure 7(b) It can be observed that, due to the viscous fingering effect and capillary action, some crude oil is displaced during water flooding, while some crude oil remains trapped in the porous medium, mainly as a film of oil adhering to the pore walls; from Figure 7 (c) It can be observed that after the nanosheet fluid displacement is completed, the amount of residual oil in the model is significantly reduced, indicating that in KH570@Ti3C2T x During the fluid displacement process of nanosheets, a large amount of crude oil is displaced. The amphiphilic Ti3C2T provided by this invention... x Flexible nanosheet oil displacement agents exhibit excellent oil displacement efficiency.

[0031] (4) Core flooding experiment Core displacement experiments were conducted using medium-permeability artificial cores (physical properties of the core samples are shown in Table 1). The cores were saturated with formation water followed by saturated crude oil (viscosity 7.73 mPa·s, 50℃), aged for 3 days, and then subjected to displacement experiments. Water was driven at a rate of 0.3 mL / min until the water cut reached 98%, and then 1 PV KH570@Ti3C2T was injected into the core at the same rate. x Nanosheet oil displacement agent (0.02wt%), calculated based on the difference between total oil recovery and waterflood recovery, KH570@Ti3C2T x The extent to which nanosheet-based oil displacement agents enhance oil recovery is shown in Table 2. The results of the enhancement of crude oil recovery by different concentrations of nanosheet-based fluid displacement agents are as follows.

[0032] Table 1 Physical properties of core samples Table 2 Amphiphilic KH570@Ti3C2T x Core displacement test results of nanosheet oil displacement agent As can be seen from the experimental results in Table 2, the amphiphilic Ti3C2T provided by this invention... x Flexible nanosheet-based oil displacement agents can effectively increase oil recovery by 4.43% to 15.21% in medium-permeability cores, and with the application of KH570@Ti3C2T... x The ability to enhance oil recovery is gradually increasing with the increase in the concentration of nanosheet oil displacement agents.

[0033] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. An amphiphilic Ti3C2T x Flexible nanosheet oil displacement agent and its preparation method, characterized in that, Includes the following steps: Step 1: By weight, add 8 parts of lithium fluoride and 100-120 parts of 12 mol / L hydrochloric acid to the reactor, heat to 40℃-50℃, and stir at a constant temperature for 15-20 min; weigh 5 parts of Ti3AlC2 and slowly add it to the reactor, stirring and reacting for 24-48 h; wash the obtained product successively with dilute hydrochloric acid and distilled water by centrifugation until the pH of the supernatant reaches about 6, thus obtaining multilayer Ti3C2T. x Nanosheets; Step 2: Centrifuge and wash the nanosheets obtained in Step 1 until the supernatant is black. Replace the distilled water with anhydrous ethanol and purge with nitrogen for 2-3 minutes. Sonicate in an ice bath for 1-2 hours. Centrifuge at 3500-5000 rpm for 15-30 minutes. The resulting black supernatant is the monolayer / few-layer Ti3C2T dispersed in the ethanol solution. x The solid content is 30%~60%; Step 3: Add the Ti3C2T obtained in Step 2 to the container. x The mixture consisted of 20 parts dispersion, 16-24 parts silane coupling agent, and 1-2 parts distilled water. The pH was adjusted to approximately 3 using acetic acid, and the reaction was carried out with stirring at room temperature for 12-24 hours. The resulting product was washed multiple times by centrifugation with anhydrous ethanol and then freeze-dried for 24-48 hours to obtain amphiphilic Ti3C2T modified with the silane coupling agent. x Flexible nanosheets; Step 4: Using distilled water as the dispersion, prepare nanofluid oil displacement agents of different concentrations using the product obtained in Step 3. Stir at room temperature for 4-8 hours at 600-800 rpm, followed by sonication in an ice bath for 1-2 hours to obtain amphiphilic Ti3C2T. x Flexible nanosheet oil displacement agent.

2. The amphiphilic Ti3C2T according to claim 1 x Flexible nanosheet oil displacement agent and its preparation method, characterized in that, The silane coupling agent is [3-(methacryloyloxy)propyl]trimethoxysilane, octyltrimethoxysilane, octyltriethoxysilane, isobutyltriethoxysilane, vinyltri(β-methoxyethoxy)silane, dodecyltrimethoxysilane, hexadecyltrimethoxysilane, and phenyltrimethoxysilane.

Citation Information

Patent Citations

  • Amphiphilic Janus nano particle and preparation method and application thereof

    CN111303853A

  • Molecular modified oleophobic hydrophilic nano oil displacement agent and preparation method thereof

    CN113773825A

  • Magnetic Mxene microbial carrier material and preparation method thereof

    CN114455690A

  • Non-ionic surfactant chemically modified nano oil displacement agent and preparation method thereof

    CN118085840A

  • Layered tackifier as well as preparation method and application thereof

    CN119220231A